المعالجة المحاسبية للأدوات المالية وأثرها على القوائم المالية -دراسة مقارنة بين IAS/9 و SCF- - إسراء, احمودة; دنيا, الأشهب; رحيمة, احثريب (جامعة الوادي - University of Eloued, 2023)
هدفت الدراسة الحالية إلى تحقيق الأمور التالية: معرفة المعايير المحاسبية الدولية الخاصة بالأدوات المالية، تحديد المفاهيم والقواعد المحاسبية المتعلقة بمحاسبة الأدوات المالية وفق النظام المحاسبي المالي، دراسة درجة التوافق بين المعايير المحاسبة الدولية والنظام المحاسبي المالي بخصوص الأدوات المالية، تباين تأثير المعالجة المحاسبية للأدوات المالية على عرض القوائم المالية. اقتصرت الدراسة على شركة مجمع صيدال، وبغية تحقيق أهداف الدراسة سابقة الذكر، فقد تم إجراؤها بالاعتماد على المنهج الوصفي ومستعينين بأسلوب التحليل بمنهج المقارنة. وتوصلت الدراسة الحالية إلى عدة نتائج نذكر أهمها:  يأثر المعيار IFRS9 على التقارير المالية؛ والقوائم المالية والتدفقات المالية  لا يوجد توافق تام بين المعايير المحاسبية الدولية والنظام المحاسبي المالي، فيما يخص المعالجة المحاسبية للأدوات المالية.  تلتزم شركة مجمع الصيدال بمتطلبات النظام المحاسبي المالي في معالجتها للأدوات المالية.  انخفاض قيمة السندات المساهمة للمساهمات وحسابات دائنة يؤدي إلى انخفاض نتيجة السنة المالية ويؤثر على جدول حساب النتائج.  تختلف متطلبات تصنيف وقياس الأصول والالتزامات المالية الواردة في المعيار IFRS9 مقارنة بالمعيار IAS39.  يقدم معيار IFRS9إضافات في المعالجة المحاسبية لأدوات المالية مقارنة بالمعيار IAS39. The current study aimed to achieve the following: knowledge of international accounting standards for financial instruments, defining accounting concepts and rules related to accounting for financial instruments according to the financial accounting system, studying the degree of compatibility between international accounting standards and the financial accounting system regarding financial instruments, the variation of the effect of accounting treatment of financial instruments on View the financial statements. The study was limited to Saidal Group Company, and in order to achieve the aforementioned study objectives, it was conducted based on the descriptive approach and using the comparative analysis method. The current study reached several results, the most important of which are:  IFRS9 affects financial reporting; financial statements and financial flows  There is no complete compatibility between international accounting standards and the financial accounting system, with regard to the accounting treatment of financial instruments;  Al-Saydal Complex Company adheres to the requirements of the financial accounting system in its handling of financial instruments;  The decline in the value of the shareholding bonds for contributions and accounts payable leads to a decrease in the result of the fiscal year and affects the results calculation schedule;  The requirements for classification and measurement of financial assets and liabilities in IFRS9 are different compared to IAS39.  The IFRS9 standard provides additions in the accounting treatment of financial instruments compared to the IAS39 standard.
Keywords: المعالجة المحاسبية،الادوات المالية،القوائم المالية